ANALISIS KORELASI PENDIDIKAN DAN PELATIHAN TERHADAP PENINGKATAN PRODUKTIVITAS KERJA INDUSTRI KECIL DAN MENENGAH ( IKM) KOTA SOLOK - Eka Hendrayani (Menara Ilmu, 2018)
The Official of Cooperative, Industry and Trade (Koperindag) in Solok City a builderinstitution for small and medium industry has been providing education and training whichaims to develop the small an medium industry in Solok City. The objective of the study isto correlation the influence of education and training given by Koperindag Solok towardthe improvement of human resources in small and medium industry. The tecknique isprocessing the data obtained from giving koesioner directly to random sample to thetrained partnert fo Koperindag Solok City and the data is processed by using SPSSprogram. The analysis in processing the data is by using validity and reliability test with asimple regression analysis. The result of study is the education and training can beoptimize the human resources (SDM) in small and medium industry (IKM) in Solok. It isindicated by the value r = + 0,883 or 88,3%. Education and training influenced 77,9%toward the human resources productivity in small and medium industry, while 22,1%caused by the other factors.Keyword : Human resources ; productivity ; education and training